2021
DOI: 10.1038/s41598-021-84524-y
|View full text |Cite
|
Sign up to set email alerts
|

Macro-, meso- and microstructural characterization of metallic lattice structures manufactured by additive manufacturing assisted investment casting

Abstract: Cellular materials are recognized for their high specific mechanical properties, making them desirable in ultra-lightweight applications. Periodic lattices have tunable properties and may be manufactured by metallic additive manufacturing (AM) techniques. However, AM can lead to issues with un-melted powder, macro/micro porosity, dimensional control and heterogeneous microstructures. This study overcomes these problems through a novel technique, combining additive manufacturing and investment casting to produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…The final shape of the cast and heat-treated (T6) samples may be visualized in Figure 1b. Overall, this process yields fine and detailed ribs/struts with a high-quality microstructure (globular 73 ± 39 µm α-Al grains, modified/refined eutectic Si and absence of significant defects) with good fabrication repeatability and anisotropic behavior [13]. This implies that fabrication-related variations in the tested samples (e.g., dimensional and microstructural changes) do not significantly affect the results of this study.…”
Section: Cellular Lattice Design and Manufacturingmentioning
confidence: 72%
See 1 more Smart Citation
“…The final shape of the cast and heat-treated (T6) samples may be visualized in Figure 1b. Overall, this process yields fine and detailed ribs/struts with a high-quality microstructure (globular 73 ± 39 µm α-Al grains, modified/refined eutectic Si and absence of significant defects) with good fabrication repeatability and anisotropic behavior [13]. This implies that fabrication-related variations in the tested samples (e.g., dimensional and microstructural changes) do not significantly affect the results of this study.…”
Section: Cellular Lattice Design and Manufacturingmentioning
confidence: 72%
“…Given that this variable is also predominantly affected by the ratio of pore volume and superficial area (Equation ( 11)) [44] and recurring to Figure 15a, it may be observed that as the value of this variable increases, there may be an elevation in the sound absorption coefficient. The frequency-dependent dynamic thermal permeability (𝑘 𝜔 ) may be calculated using Equation (13), being dependent on the differentials of pressure and time (𝜕𝑃/𝜕𝑡), porosity (Ф), air thermal conductivity (k) and excess of the temperature inside the cellular The frequency-dependent dynamic thermal permeability (k (ω)) may be calculated using Equation (13), being dependent on the differentials of pressure and time (∂P/∂t), porosity (Φ), air thermal conductivity (k) and excess of the temperature inside the cellular solid (τ) [40,42]. The static thermal permeability (k 0 ) relates thermal effects between the rigid frame and the fluid at low frequencies actuating in the boundary layer, according to Equation ( 13) [45].…”
Section: Resultsmentioning
confidence: 99%
“…This effect cannot be detected in investment cast open-cell metal foams, where reticulated polymer foams or additively manufactured optimized lattice structures have been used as sacrificial templates, as a much lower node-to-strut thickness ratio is given. [28,39,40] The solidification and following quenching of the cast foams resulted in a variation of the grain size of the microstructure of α-Al along the melt flow direction (Figure 4). Different cooling rates in the foam after casting, due to high heat capacities of the investment material and mass accumulation of molten metal in the feeding system, are the reasons for this behavior.…”
Section: Manufacturing Resultsmentioning
confidence: 99%
“…additive manufacturing. [27,28] In the case of additively manufactured sacrificial structures, the problem of high-volume scalability remains. In terms of reticulated foams, PU or PE foams are commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…Investment casting (IC) is becoming increasingly popular among materials scientists to create near-net-shape products with enhanced surface finish and dimensional stability. 5 Another advantage of using the IC process is composite materials with intricate shapes with poor machinability and workability. 6 Recent studies have reported using the fused deposition modeling (FDM) process to fabricate sacrificial patterns required for the IC process.…”
Section: Introductionmentioning
confidence: 99%